Animal health syndromic surveillance system in Jordan, a road map for a pilot model - De Nardi, M.; Küker, S.; Salah, S.; Qtananni, I.; Rosso, F.; Baiomy, S. (Frontiers in Veterinary Science, 2025)
Introduction and objectivesEarly detection of transboundary animal diseases (TADs) is critical to mitigating economic losses and safeguarding food security. These diseases pose significant threats to regions including North Africa, the Near East, and Southeast Europe. Recognizing the importance of early detection, the European Commission for the Control of Foot-and-Mouth Disease, in collaboration with SAFOSO AG, launched a multiphases project to introduce syndromic surveillance system (SyS) in the Near East, with Jordan eventually selected as the pilot country. In Jordan, therefore, the project aimed to enhance disease surveillance capabilities through the design and implementation of a pilot SyS.Project’s elementsInitially, a scoping review of global SyS initiatives was conducted, with a specific focus on North Africa, Southeast Europe and the Near East. This was followed by a regional workshop in Beirut, Lebanon, where SyS concepts were introduced to regional stakeholders. During this workshop Jordan was selected for the SyS pilot study. The final phase involved the development of a tailored pilot SyS in Jordan which included extensive stakeholder engagement through workshops and virtual follow-ups. Key technical activities encompassed syndrome definition, evaluation of data availability and data access, selection of appropriate statistical methodology. Governance was established through the formation of steering and technical committees, and supported by a communication strategy for effective dissemination of findings. A road map was developed to monitor the pilot syndromic surveillance initial implementation and long-term progresses.ResultsThe pilot SyS in Jordan was designed to integrate diverse data sources, including clinical and laboratory reports, slaughter statistics, livestock production data, public health information and animal movement records. Designed to prioritise early detection, it included comprehensive data collection, rigorous analysis, and systematic dissemination. The design of this pilot SyS in Jordan highlights its feasibility and benefits for early disease detection, driven by strong stakeholder engagement, legal framework alignment, and robust information technology infrastructure.ConclusionThe successful implementation of the pilot SyS in Jordan underscores its potential as a model for other countries in the region. The project has enhanced capacity for disease surveillance, supporting TADs control and prevention. Sustained collaboration, capacity development, and monitoring will be essential for scaling the SyS at national level and ensuring long-term success in combating transboundary animal diseases.